An adaptive probabilistic mapping matrix search algorithm for vulnerability analysis of PPS. (September 2019) - Yang, Jun; Wang, Jun; Wei, Guanxiang; Yang, Ming; Lu, Hongxing
Highlights: A probabilistic mapping algorithm is presented for vulnerable analysis of PPS. The adversary transition is regarded as stochastic risk-taking path choice behaviors. Practice is illustrated with a hypothetical facility for path planning analysis. The algorithm is effective for performance evaluation and optimization of PPS. Abstract: The paper presents an adaptive probabilistic mapping matrix search algorithm for adversary path planning and vulnerability analysis of physical protection system. The algorithm represents the adversary transition process as stochastic risk-taking path choice behaviors under uncertainties. The interactions among the protective elements are characterized by a full probabilistic mapping scheme of discretized Cell-to-Cell transitions across the area of physical protection for path planning analysis. Practice of the proposed algorithm is demonstrated with a hypothetical case of nuclear facility for risk-significant adversary path identification. The analysis results show that the method is capable of path search analysis for determining the system effectiveness measures.